Utilization of Curcuma Molases Block to Increase The Performance of Goats that Infected Gastrointestinal Worm at Wonorejo, Wates District, Kediri Regency - Hani Plumeriastuti; Poedji Hastutiek; Lucia Tri Suwanti; Wiwik Misaco Yuniarti; Nusdianto Triakoso; Arimbi Arimbi (Journal of Parasite Science (JoPS), 2018)
This was a Community Service activity that aims to share knowladge about utilization of Curcuma Molasses Block (CMB) to increase performance of goats that infected gastrointestinal (GI) parasites to The Goat Breeder Group at  Wonorejo, Wates District, Kediri Regency. The activities include: counseling about raising goat management, presentasion on worm diseases that infect goats and CMB as anthelmentic, workshop and practice to make CMB, detection egg worm in goat`s feces, treatment on infected goats and filling out questionnaires evaluating the performance of goat before and after giving CMB. The result show that all of feces samples were positive contain egg worms of  Haemonchus contortus, Chabertina ovina, Trichuris globulosa, Strongyloides papillosus, Fasciola gigantica, Trichostrongylus spp., Toxocara sp., and Oesohagustomum columbianum even also protozoans  Eimeria sp., and Blastocystis sp. Administration CMB increase performance of worm-infected goats which indicated by increase in appetite, soft and shiny hair and the body more well-fed.